2022
DOI: 10.3390/jcm11175039
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial Enhanced Fluence Pulsed Light M Accelerated Crosslinking for Early Progressive Keratoconus with Chemically Enhanced Riboflavin Solutions and Air Room Oxygen

Abstract: Purpose: To assess the 3-year clinical results of the 18 mW 7 J/cm2 transepithelial enhanced fluence pulsed light M accelerated crosslinking in the treatment of progressive keratoconus (KC) with chemically enhanced hyper-concentrated riboflavin solutions without iontophoresis and with air-room oxygenation. Setting: Siena Crosslinking Center, Siena, Italy. Methods: Prospective pilot, open non-randomized interventional study including 40 eyes of 30 young adult patients over 21 years old (10 simultaneous bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
(71 reference statements)
2
10
0
Order By: Relevance
“…The progressively higher fluence protocols enhance Epi-Off and Epi-On efficacy, as demonstrated in past and recent literature ( 9 12 , 15 ). The increased fluence variance may be the key to optimizing the photodynamic process of Epi-On crosslinking, paving the way to the final switch ( 9 ). We present the preliminary data of the new pachymetry-based progressively higher fluence Epi-On nomogram as a new paradigm of corneal photodynamic therapy for early progressive KC ( 22 24 ).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…The progressively higher fluence protocols enhance Epi-Off and Epi-On efficacy, as demonstrated in past and recent literature ( 9 12 , 15 ). The increased fluence variance may be the key to optimizing the photodynamic process of Epi-On crosslinking, paving the way to the final switch ( 9 ). We present the preliminary data of the new pachymetry-based progressively higher fluence Epi-On nomogram as a new paradigm of corneal photodynamic therapy for early progressive KC ( 22 24 ).…”
Section: Introductionsupporting
confidence: 67%
“…What is even more relevant is the absence of risks and adverse events, which place this method amongst the prophylactic therapies of primary and iatrogenic corneal ectasia as it can be applied purely preventively, even in cases of ectasia that have not yet evolved, to safeguard patients' vision with excellent compliance. The approach also allows for the possibility of simultaneous outpatient interventions, causing minimal postoperative discomfort and avoiding microstructural damage to the ocular surface so that patients may return to their normal activities the day after ( 9 ). The high fluence era began in 2016, with studies on customized CXL by Seiler (the first study with 10 J/cm 2 ) ( 11 ) and Mazzotta (the first study with PiXL at 10 and 15 J/cm 2 ) ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We, therefore, concluded that this protocol is not suitable for halting keratoconus disease progression. Possible means of improving the efficacy of the iontophoresis-assisted protocol include a longer irradiation time, the addition of oxygen during treatment, or pulsed UV-A irradiation 48. We also concluded that the way in which progressive keratoconus is diagnosed, and the way in which treatment efficacy is evaluated, significantly affect the interpretation of the outcome.…”
Section: Discussionmentioning
confidence: 81%
“…Possible means of improving the efficacy of the iontophoresis-assisted protocol include a longer irradiation time, the addition of oxygen during treatment, or pulsed UV-A irradiation. 48 We also concluded that the way in which progressive keratoconus is diagnosed, and the way in which treatment efficacy is evaluated, significantly affect the interpretation of the outcome. These aspects should be considered in future clinical investigations of CXL.…”
Section: Discussionmentioning
confidence: 90%